Impact of a Six-Week Naturopathic Regimen on Pain, Inflammation, and Quality of Life in a Patient with Rheumatoid Arthritis: A Case Study - Soundarapandiyan, Sabeetha; Manoharan, Thiruchitrampalam; Sivadas Karanchery, Shilpa; V Ravindran, Dhilip (Indian Journal of Integrative Medicine, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder that leads to joint inflammation, pain, and potential damage, with significant disability and systemic involvement. Conventional treatments often carry adverse effects, prompting interest in complementary and alternative medicine (CAM) therapies like yoga and naturopathy. This case study evaluates the impact of a six-week naturopathic regimen, including massage therapy, reflexology, hot baths, mustard packs, and cupping, on a 34-year-old female with RA. Following treatment, the patient showed significant improvements in inflammatory markers (ESR, CRP, Anti-CCP) and reduced depression symptoms (PHQ-9). The therapies appeared to enhance circulation, modulate pain-relieving neurotransmitters, and decrease pro-inflammatory cytokines. The findings suggest that yoga and naturopathy may effectively complement conventional RA treatments, improving pain, inflammation, and overall quality of life.